2015
DOI: 10.7314/apjcp.2015.16.4.1529
|View full text |Cite
|
Sign up to set email alerts
|

Sun Burn Incidence and Knowledge of Greek Elementary and High School Children about Sun Protection

Abstract: Introduction: Overexposure to sun radiation and particularly its accumulation during childhood and adolescence is a significant risk factor for skin cancer development. The sun burn is particularly important. Aim: To estimate sun burn incidence in young pupils in a coastal area of Greece. Materials and Methods: Two surveys were conducted in a school population in the same district in Greece, over different periods of time, in young people 9 to 18 years old (n=2 977). Anonymous questionnaires were completed. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 52 publications
0
7
0
3
Order By: Relevance
“…Al-Naggar also reported that Malaysian road traffic police officers had poor practice regarding application of sunscreen (Al-Naggar, 2013). Several studies showed greater practice in terms of skin cancer prevention than those observed in our study (Vries et al, 2005;Saridi et al, 2015). Therefore, there is a need to develop health education programs to train college students in the area of skin cancer and its preventive strategies.…”
Section: Discussionmentioning
confidence: 39%
“…Al-Naggar also reported that Malaysian road traffic police officers had poor practice regarding application of sunscreen (Al-Naggar, 2013). Several studies showed greater practice in terms of skin cancer prevention than those observed in our study (Vries et al, 2005;Saridi et al, 2015). Therefore, there is a need to develop health education programs to train college students in the area of skin cancer and its preventive strategies.…”
Section: Discussionmentioning
confidence: 39%
“…Because of that, the next question in the survey was to obtain information on the frequency of experienced sunburn in the past, which is also a melanoma risk factor. The skin sensitivity in young age, as well as frequently spending time outdoors and the fact that children have less developed skin pigmentation and immune system, result in greater risk of developing melanoma in adulthood [8]. Even one episode of sunburn increases it about 1.5 to 3 times, while over 5 episodes increase it as much as 2 to 5 times [8].…”
Section: Discussionmentioning
confidence: 99%
“…The survey was shared with students from two Polish medical universities and with students from many more non-medical faculties at different universities in Poland. In total, 277 students responded: 111 (40%) from medical faculties (med), including medical (102 responders), dentistry (8) and pharmacy faculty (1), and 166 (60%) from non-medical faculties (n/med) including other sciences (not medicine-related) and humanities. They answered 17 questions, general and specific, regarding melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…The questions of the learning survey were specifically designed for this study by a dermatologist doctor, based on their clinical background and on a literature review including scholarly articles, reviews and original research related to the affects of individual behaviors regarding sun exposure [ 28 , 29 , 30 ]. It is an anonymous self-reported learning survey [ 8 , 9 , 12 , 14 , 15 ] to collect information about knowledge and practices concerning solar exposure from the students who have already attended the “Education for Health” curricular unit. The learning survey was distributed to twenty students from the same institution (not included in the study).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most popular sun protection measures is the use of sunscreen. It has been demonstrated that deleterious effects on the skin from excessive sun exposure are cumulative [ 7 ] and it is estimated that six out of 10 cases of skin cancer are related to excessive sun exposure [ 8 ]. Non-melanoma skin cancer, and specifically basal cell carcinoma and squamous cell carcinoma, are the most common cancers in the Caucasian race and scientific literature suggests that “the incidence of this type of cancer could be prevented if individuals adopted precautionary behaviors” [ 9 ] (p. 37).…”
Section: Related Workmentioning
confidence: 99%